Breast cancer and breast screening: perceptions of Chinese migrant women living in New Zealand - Zhang W; Rose SB; Foster A; Pullon S; Lawton B (CSIRO Publishing, 2014)
INTRODUCTION: Migrant Chinese constitute a significant and increasing proportion of New Zealand women. They have lower rates of participation in breast cancer screening than other New Zealanders, but reasons for this are unknown. The aim of this study was to investigate factors affecting Chinese women's understanding of, and access to, breast health services, to better understand reasons for low participation in screening and their experiences of breast cancer clinic care. METHODS: The participants were 26 Chinese migrant women-19 recruited in the community and seven recruited from 17 eligible women attending a breast clinic between 2008 and 2010 in Wellington, New Zealand. The design was that of a qualitative study, using semi-structured interviews and thematic content analysis. FINDINGS: There were low levels of awareness about the national breast screening programme and limited engagement with preventive primary care services. Concerns about privacy and a range of communication difficulties were identified that related to oral language, lack of written information in Chinese, and limited understanding about Chinese perceptions of ill health and traditional Chinese medicine by New Zealand health professionals. CONCLUSION: Addressing communication barriers for Chinese migrant women has the potential to raise awareness about breast cancer and breast health, and to increase successful participation in breast cancer screening. Greater efforts are needed to ensure this group has an understanding of, and is engaged with a primary care provider. Such efforts are key to improving health for this growing sector of the New Zealand population.